Ferðalok - Arnaldur Indriðason 1961- (Vaka-Helgafell, 2024)
"This is a historical novel about the national poet Jónas Hallgrímsson by one of Iceland's most popular authors. His upbringing in a small farm in the north of Iceland and his life in the big city in Copenhagen. Jónas lies sick in bed after his, what would be fatal, accident and looks back to his home in Iceland."